Twelfth Malaysia Plan : Prospective Impacts on Urban and Regional Development - Jamalunlaili, Abdullah; Khalid, Zanudin; Marlyana Azyyati, Marzukhi (Malaysian Institute of Planners, 2022)
The Malaysia Plan is a five-year development plan that comprises policies and strategies to guide the government to achieve desired economic and socio-economic goals. The first Malaysia Plan started in 1966 following the inclusion of Sabah and Sarawak in 1963, followed by consecutive plans until the present 12th Malaysia Plan (RMK12, 2021–2025). The last ten years have shown a significant shift by the Malaysian government in emphasising the importance of urban and regional planning in shaping the national development policies and strategies. This paper analyses policies and strategic projects proposed in RMK12 that relate to urban and regional development and their likely impacts on the spatial development of the nation. The present study employs conventional content analysis as its main method. In addition, RMK12 policies and strategic projects are linked to the thrusts of Rancangan Fizikal Negara 4 (RFN4) and the principles of Dasar Perbandaran Negara 2 (DPN2). The findings demonstrated existing links between the policies and strategic projects of RMK12 and the thrusts of RFN4 and the principles of DPN2. Additionally, the spatial focus of RMK12 projects on the Klang Valley and Sabah and Sarawak indicates the government’s commitment to leverage the economic potential of cities and the need to reduce regional development disparity between Peninsular Malaysia and Sabah and Sarawak. The findings will assist stakeholders in better understanding the implications and significance of the policies and strategic projects highlighted in RMK12 for Malaysian urban and regional development, and will thus drive the country toward achieving sustainable and inclusive development.